Development of Electronic Student Worksheet Based on Multiple Intelligence on Acid Base Material to Improve Students’ Logical Mathematical and Interpersonal Intelligence - Eyza Alifia; Sri Wardani (Universitas Negeri Semarang, 2026)
This study aims to determine the characteristics, feasibility, and effectiveness of a Multiple Intelligence-based Electronic Student Worksheet (E-LKPD) on acid-base material in enhancing students' logical-mathematical and interpersonal intelligences. The research method employed is the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. The instruments used in this study comprise logical-mathematical intelligence tests (pre-test and post-test), interpersonal intelligence observation sheets, and student response questionnaires. Data on students' logical-mathematical intelligence from the pre-test and post-test were analyzed using the N-Gain test, while improvement in interpersonal intelligence was evaluated through observation conducted at the beginning and end of the learning process. Feasibility testing of the E-LKPD by content experts and media experts yielded scores of 98.76% and 96.11%, respectively, both categorized as highly valid. The readability test resulted in a score of 86%, indicating a very good level of readability. The analysis of logical-mathematical intelligence improvement showed an N-Gain score of 0.60, categorized as moderate. Students' interpersonal intelligence also increased, with average scores of 76.29% in the good category and 82.73% in the very good category. Based on these findings, it can be concluded that the Multiple Intelligence-based E-LKPD on acid-base material is feasible and effective in enhancing students' logical-mathematical and interpersonal intelligences.